Risk factors of phlebitis in patients admitted to the intensive care unit vary according to the duration of catheter dwelling: A post-hoc analysis of the AMOR-VENUS study - Yutaro Shinzato; Hideto Yasuda; Takashi Moriya; Haruka Taira; Yuki Kishihara; Masahiro Kashiura; Yuki Kotani; Natsuki Kondo; Kosuke Sekine; Nobuaki Shime; Keita Morikane (PLoS ONE, 2025)
Aim This study investigated the risk factors of peripheral intravenous catheter (PIVC)-related phlebitis in critically ill patients according to the duration of catheter dwelling. Methods This was a post-hoc analysis of the AMOR-VENUS study involving 23 intensive care units (ICUs) in Japan. We included patients aged ≥ 18 admitted to the ICU and had PIVCs inserted during ICU admission. The primary outcome measure was phlebitis, and the risk factors of phlebitis were evaluated based on hazard ratios (HR) and 95% confidence intervals (CI). The duration of catheter dwelling was classified as (i) ≤ 24 h; (ii) > 24 h, ≤ 72 h; and (iii) > 72 h. Multivariable marginal Cox regression analysis was performed using the presumed risk factors for each group. Results In total, 1,335 patients and 3,348 PIVCs were evaluated. Among patients with ≤ 24 h of catheter dwelling, phlebitis occurrence was associated with ICU admission for non-surgical management with ICU admission for elective surgery as the reference, standardized drug administration in the ICU, and dexmedetomidine administration in the ICU. Among those with > 24 h but ≤ 72 h of catheter dwelling, it was associated with male sex with female sex as the reference, tetrafluoroethylene as the catheter material with polyurethane as the reference, nicardipine administration, and noradrenaline administration. Among those with > 72 h of catheter dwelling, it was associated with a catheter size ≥ 18 G and nicardipine administration. Conclusion The risk factors for phlebitis varied with the duration of catheter dwelling. Individualized catheter management, considering the duration of catheter dwelling, may help avoid phlebitis in patients admitted to the ICU.